The Factors Influence the SNS Switching of Chinese Students Who Study in Malaysia - Liu, Jiachi (2014)
This study focuses on determining the significance of the factors which influence Chinese student users’ intention to switch between SNSs, to analyze the reasons for the inability Chinese SNSs to hold and retain their users. This research used quantitative. 220 questionnaires were distributed to the respondents in those four universities. The respondents are individuals from China who are currently studying in Malaysia. Of the 220 questionnaires distributed, 200 were completed and returned. The data were analyzed using SPSS software version 20. Factor analysis and reliability testing were conducted to test the validity and reliability of the questions before proceeding in analyzing the data. In order to check the relationship and significance of the independent variables to the dependent variable, correlation, linear regression, and multiple regression analysis were used. Based on the results of this study, dissatisfaction, switching cost and relative attractiveness are all significant factors which has influence with the dependent variable: Switching Intention. In addition, both dissatisfaction and relative attractiveness are positively correlated with switching intention. Switching cost is the only one negative factor in this study.